2020
DOI: 10.5664/jcsm.8734
|View full text |Cite
|
Sign up to set email alerts
|

Dream enactment behavior: review for the clinician

Abstract: Dream enactment behavior commonly occurs on occasion in normal children and adults. Disruptive and frequent dream enactment behavior may come to the attention of the clinician either as the primary reason for consultation or as a prominent characteristic of a patient with other sleep disorders. Questioning patients with chronic neurologic and psychiatric disorders may also reveal previously unrecognized behavior. In the absence of sleep pathology, process of dream enactment likely begins with active, often emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 314 publications
(280 reference statements)
2
19
1
Order By: Relevance
“…The difference might be due to sample size, and the population of interest. The prevalence of DEB in our study is lower than studies among other population as observed in postpartum women (63%) and pregnant (40%) women [22] whereas our finding is far higher than studies in the general adult population (5.9% in men, and 4.1% in women), older adults (10.9%) [31]. This difference might be accounted for the varying activities of the population.…”
Section: Plos Onecontrasting
confidence: 83%
See 1 more Smart Citation
“…The difference might be due to sample size, and the population of interest. The prevalence of DEB in our study is lower than studies among other population as observed in postpartum women (63%) and pregnant (40%) women [22] whereas our finding is far higher than studies in the general adult population (5.9% in men, and 4.1% in women), older adults (10.9%) [31]. This difference might be accounted for the varying activities of the population.…”
Section: Plos Onecontrasting
confidence: 83%
“…The knowledge of DEB is helpful to design intervention and prevention strategies for neurological disorders [12]. Moreover, it has imminent function to prevent α-synucleinopathy-related motor and cognitive decline [13] and to innovate therapeutic options for clinicians [14]. Evidences showed violent behavior during sleep exist in 1.6% among adults of whom 78.7% reported vivid dreams and 31.4% hurt themselves or someone else [15].…”
Section: Introductionmentioning
confidence: 99%
“…In our sample, they could be related to the emotional impact denoted by increased anxiety and depression symptoms during MSI stressful conditions. The necessity of characterizing the phenomenology of dream enacting behaviors had been pointed out by two recent and excellent reviews 64 , 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…The intrusion of REM sleep in wakefulness may also occur at the post-traumatic stress disorder, and other sleep disorders, that share the possibility of body enact dream content and it underlies oneiric experience that can be expressed by dream enactment behavior. Many recent works shed light on this question (Baltzan et al, 2020;Barone, 2020;Elliott et al, 2020;Rocha and Arnulf, 2020;Siclari et al, 2020).…”
Section: Lady Macbeth's Nightly Ambulatory Behaviormentioning
confidence: 99%